Clickable Vitamins as a New Tool to Track Vitamin A and Retinoic Acid in Immune Cells - Bos, Amelie V.; Erkelens, Martje N.; Koenders, Sebastiaan T.A.; van der Stelt, Mario; van Egmond, Marjolein; Mebius, Reina E. (Frontiers in Immunology, 2021)
The vitamin A derivative, retinoid acid (RA) is key player in guiding adaptive mucosal immune responses. However, data on the uptake and metabolism of vitamin A within human immune cells has remained largely elusive because retinoids are small, lipophilic molecules which are difficult to detect. To overcome this problem and to be able to study the effect of vitamin A metabolism in human immune cell subsets, we have synthesized novel bio-orthogonal retinoid-based probes (clickable probes), which are structurally and functionally indistinguishable from vitamin A. The probes contain a functional group (an alkyne) to conjugate to a fluorogenic dye to monitor retinoid molecules in real-time in immune cells. We demonstrate, by using flow cytometry and microscopy, that multiple immune cells have the capacity to internalize retinoids to varying degrees, including human monocyte-derived dendritic cells (DCs) and naïve B lymphocytes. We observed that naïve B cells lack the enzymatic machinery to produce RA, but use exogenous retinoic acid to enhance CD38 expression. Furthermore, we showed that human DCs metabolize retinal into retinoic acid, which in co-culture with naïve B cells led to of the induction of CD38 expression. These data demonstrate that in humans, DCs can serve as an exogenous source of RA for naïve B cells. Taken together, through the use of clickable vitamins our data provide valuable insight in the mechanism of vitamin A metabolism and its importance for human adaptive immunity.